Pelatihan Media Pembelajaran Berbasis Geogebra Bagi Guru Matematika dan Ipa - Paiz Jalaludin; Krishna Prafidya Romantica; Alrafiful Rahman; Ani Nuraini (Jurnal Pengabdian Masyarakat (Bisma), 2023)
Technology-based learning media is one of the important things in learning Mathematics and Science in schools. It aims to create a fun, creative and innovative learning atmosphere so as to increase student motivation and learning outcomes. One of the learning media for Mathematics and Science that is often used is the GeoGebra application, which is the application of Mathematics in the study of geometry and algebra. However, previous data and research show that there is still a lack of mastery of Mathematics and Science teachers in using the software, especially in the location of service partners, namely in Darunnajah elementary, junior high, and high school schools, Jakarta. Therefore, the service proposed to carry out service in the form of training on the use of the GeoGebra application for teachers as a solution to these problems. The service activities ran smoothly, both in terms of preparation, implementation, and evaluation. This is shown by the results of a two-way evaluation between service and service partners. Participants are able to answer and practice directly the material presented in the evaluation session. In addition, based on the answers to the satisfaction / approval questionnaire, the participants' satisfaction with the activities carried out reached a fairly high average, reaching 87.80%.